Metformin Reduces Inflammatory Markers Through AMPK Activation in Type 2 Diabetes Patients - Al-din, Khitam Hassan Saleh Salah (Academia Open, 2025)
General Background: Type 2 diabetes mellitus represents a complex metabolic disorder characterized by chronic hyperglycemia and systemic inflammation. Specific Background: Metformin, derived from Galega officinalis, has served as first-line pharmacotherapy for over six decades, demonstrating efficacy in glycemic control through multiple mechanisms including AMPK activation and mitochondrial modulation. Knowledge Gap: Despite extensive clinical application, the precise molecular pathways underlying metformin's anti-inflammatory properties and their relationship to improved metabolic outcomes remain incompletely characterized. Aims: This systematic review examined metformin's effects on inflammatory biomarkers in patients with type 2 diabetes, focusing on molecular mechanisms involving AMPK activation, mitochondrial function, and oxidative stress reduction. Results: Analysis of multiple studies revealed significant reductions in C-reactive protein, high-sensitivity CRP, TNF-α, and IL-6 levels, alongside decreased leukocyte-endothelial interactions through diminished expression of ICAM-1 and E-selectin adhesion molecules. Novelty: This review synthesizes emerging evidence on brain-dependent pathways involving Rap1 protein modulation and identifies metformin's dual role in glycemic control and inflammation suppression. Implications: These findings support metformin's multifunctional therapeutic potential beyond diabetes management, with applications in cardiovascular protection, cancer prevention, and inflammatory disease modification.HIghlight : Metformin reduces blood glucose and inflammatory markers (CRP, HSCRP) in type 2 diabetes patients through AMPK activation. The drug works via mitochondrial Complex I inhibition, mTORC1 suppression, and CARM1 enzyme modulation. Pharmacogenetic testing for CYP450 enzymes predicts individual drug responses and adverse effects for personalized treatment. Keywords : Metformin, Type 2 Diabetes, AMPK, Inflammatory Markers, Molecular Mechanisms